Identification of Glycyrrhiza as the rikkunshito constituent with the highest antagonistic potential on heterologously expressed 5-HT3A receptors due to the action of flavonoids - Herbrechter, Robin; Ziemba, Paul M.; Hoffmann, Katrin M.; Hatt, Hanns; Werner, Markus; Gisselmann, Guenter (Frontiers in Pharmacology, 2015)
The traditional Japanese phytomedicine rikkunshito is traditionally used for the treatment of gastrointestinal motility disorders, cachexia and nausea. These effects indicate 5-HT3 receptor antagonism, due to the involvement of these receptors in such pathophysiological processes. E.g. setrons, specific 5-HT3 receptor antagonists are the strongest antiemetics, developed so far. Therefore, the antagonistic effects of the eight rikkunshito constituents at heterologously expressed 5-HT3A receptors were analyzed using the two-electrode voltage-clamp technique. The results indicate that tinctures from Aurantii, Ginseng, Zingiberis, Atractylodis and Glycyrrhiza inhibited the 5-HT3A receptor response, whereas the tinctures of Poria cocos, Jujubae and Pinellia exhibited no effect. Surprisingly, the strongest antagonism was found for Glycyrrhiza, whereas the Zingiberis tincture, which is considered to be primarily responsible for the effect of rikkunshito, exhibited the weakest antagonist of 5-HT3A receptors. Rikkunshito contains various vanilloids, ginsenosides and flavonoids, a portion of which show an antagonistic effect on 5-HT3 receptors. A screening of the established ingredients of the active rikkunshito constituents and related substances lead to the identification of new antagonists within the class of flavonoids. The flavonoids (-)-liquiritigenin, glabridin and licochalcone A from Glycyrrhiza species were found to be the most effective inhibitors of the 5-HT-induced currents in the screening. The flavonoids (-)-liquiritigenin and hesperetin from Aurantii inhibited the receptor response in a non-competitive manner, whereas glabridin and licochalcone A exhibited a potential competitive antagonism. Furthermore, licochalcone A acts as a partial antagonist of 5-HT3A receptors. Thus, this study reveals new 5-HT3A receptor antagonists with the aid of increasing the comprehension of the complex effects of rikkunshito.